Effects of using reducts in the performance of the irbasir algorithm (2013)
Feature selection is a preprocessing technique with the objective of fi nding a subset of attributes that improve the classifi erperformance. In this paper, a new algorithm (IRBASIRRED) is presented for the generation of learning rules that uses feature selection toobtain the knowledge model. Also a new method (REDUCTSIM) is presented for the reduct’s calculation using the optimization technique,Particle Swarm Optimization (PSO). The proposed algorithm was tested on data sets from the UCI Repository and compared with thealgorithms: C4.5, LEM2, MODLEM, EXPLORE and IRBASIR. The results obtained showed that IRBASIRRED is a method that generatesclassifi cation rules using subsets of attributes, obtaining better results than the algorithm where all attributes are used.